A 2D-g-C3N4 nanosheet as an eco-friendly adsorbent for various environmental pollutants in water. (March 2017) - Cai, Xingguo; He, Junyong; Chen, Liang; Chen, Kai; Li, Yulian; Zhang, Kaisheng; Jin, Zhen; Liu, Jinyun; Wang, Chengming; Wang, Xuguang; Kong, Lingtao; Liu, Jinhuai
Abstract: A novel graphitic carbon nitride (g-C3 N4 ) nanosheet adsorbent with a large surface area, remarkable hydrophilicity and high adsorption capacity, was presented for the removal of cadmium ions (Cd 2+ ) and methylene blue (MB) from aqueous solution. Adsorption measurements were conducted systematically to study the influences of the contact time, initial concentrations of Cd 2+ and MB, temperature, and pH value. The maximum adsorption capacities of g-C3 N4 towards Cd 2+ and MB were 94.4 and 42.1 mg g −1, respectively, at 318.5 K when the initial concentrations of Cd 2+ and MB were 200 and 20 mg L −1, respectively. The adsorption kinetics fit a pseudo-second-order model. The high adsorption performance of the g-C3 N4 adsorbent can be attributed to the multiple adsorption sites on g-C3 N4, including the π-π conjugate interactions and electrostatic attractions with pollutants in water. In addition, it is significant to achieve high adsorption performance of g-C3 N4 nanosheets by efficiently exposing the adsorption sites by adjusting the microstructure surface properties and dispersity in solution. Graphical abstract: Highlights: An eco-friendly adsorbent 2D-g-C3 N4 was prepared through simple pyrolysis. 2D-g-C3 N4 can effectively remove Cd 2+ and MB from water. The adsorption mechanisms of Cd 2+ and MB were proposed.